Pellet plant energy simulator. Issue 1 (January 2016) - Bordeasu, D; Pulido, T Vasquez; Nielsen, C
Abstract: The Pellet Plant energy simulator is a software based on advanced algorithms which has the main purpose to see the response of a pellet plant regarding certain location conditions. It combines energy provided by a combined heat and power, and/or by a combustion chamber with the energy consumption of the pellet factory and information regarding weather conditions in order to predict the biomass consumption of the pellet factory together with the combined heat and power, and/or with the biomass consumption of the combustion chamber. The user of the software will not only be able to plan smart the biomass acquisition and estimate its cost, but also to plan smart the preventive maintenance (charcoal cleaning in case of a gasification plant) and use the pellet plant at the maximum output regarding weather conditions and biomass moisture. The software can also be used in order to execute a more precise feasibility study for a pellet plant in a certain location. The paper outlines the algorithm that supports the Pellet Plant Energy Simulator idea and presents preliminary tests results that supports the discussion and implementation of the system